A Study on Tax Planning Strategies Implemented by Salaried Assessees in Mumbai City - Ramraj Tiwari, Sanjay Kumar; Verma, Deepak (Journal of Neonatal Surgery, 2025)
Tax planning plays a crucial role in financial decision-making for salaried individuals, helping them optimize their tax liability while ensuring long-term financial stability. This study examines the tax planning measures adopted by salaried assesses in Mumbai City, analysing variations based on age, income level, and awareness. The research aims to assess the level of awareness regarding tax-saving options, identify the impact of tax planning on savings behaviour, and explore the challenges faced by taxpayers. The findings indicate that middle-income earners (₹5,00,000 – ₹10,00,000) form the largest group actively engaging in tax-saving investments, primarily under Section 80C (PPF, LIC, ELSS) and HRA exemptions. High-income earners focus on advanced tax-saving strategies, such as NPS, tax-free bonds, and business deductions. However, the study highlights a significant lack of awareness among taxpayers, leading to underutilization of deductions and inefficient tax planning. Challenges such as complex tax regulations, lack of employer guidance, and limited financial advisory support hinder effective tax planning. The study recommends simplifying tax laws, increasing awareness programs, encouraging financial advisory services, and promoting diversified tax-saving investments to enhance tax efficiency. Strengthening financial literacy and targeted policy reforms can help taxpayers maximize their savings and improve financial well-being. This research underscores the need for a comprehensive approach to tax planning, ensuring salaried individuals make informed financial decisions while complying with tax laws effectively.